Pengaruh Firm Size, Return On Asset dan Leverage Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2015-2019 - Agusti Nabilla; Rachmawati Meita Oktaviani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to see how company size, return on assets, and leverage affect tax evasion. This research is a type of quantitative research that uses secondary data in the form of financial reports from the official website of the Indonesia Stock Exchange. The population in this study are manufacturing companies listed on the IDX for the 2015-2019 period. The sample was selected from the purposive sampling method for 5 years so as to get 30 companies from several criteria. This study uses panel data regression analysis with random effect model estimation with the help of the Eviews version 12 program. Based on the results of this study it shows that company size has no effect on tax evasion. Meanwhile, return on assets and leverage have an influence on tax avoidance.